Evaluasi Ketercapaian Standar Penjaminan Mutu Penelitian Di Program Studi D3 Mesin Otomotif Universitas Muhammadiyah Magelang Dengan Metode Indeks - Setiyo, Muji; Waluyo, Budi; Saifudin, .; Purnomo, Bagiyo Condro; Munahar, Suroto; Widodo, Noto; Rusdjijati, Retno (LPM IHDN Denpasar, 2018)
In the past decade, the general method for measuring the performance of research and scientific publications in a Study Program at a Higher Education is by the Rough Value (Nilai Kasar, NK) calculated per three years. This value is derived from the accreditation instrument. In fact, the calculation of the performance of research and scientific publications with NK cannot represent an annual performance. Therefore, this paper presents a new method for calculating research and scientific publications performance with an index (IP-PS and IPub-PS), which is calculated annually. An example of quality measurement practice in the Automotive Diploma Program of Universitas Muhammadiyah Magelang. As a result, calculations with IP-PS and IPub-PS are more likely to present real conditions per year than using NK.